Triboluminescence and triboelectricity: toward next-generation wearable light sources - Yuan, Shuoxun (Nanyang Technological University, 2023)
Due to its good performance and excellent output characteristics, the application of triboelectricity nanogenerator (TENG) in the field of intelligent motion is becoming more and more widespread, and the research and exploration in this field are also constantly developing. This paper systematically summarizes the application of TENG in the field of intelligent sports from three aspects: principle and mechanism, application form and output performance, including theoretical analysis, concrete cases and innovative application examples. First, we introduce the basic physical principles and four main working modes of TENG and their working mechanisms, including the diatomic model, Maxwell current, contact charging, four working modes, etc. Next, this paper focuses on the combination and application of TENG in the field of intelligent sports from the two directions of daily exercise and competitive sports, including the following contents: general underlying application logic, specific application cases of different kinds of sports, and technical modules that should be paid attention to in application, etc. Then, the output performance of TENG is discussed in this paper. This part includes the following contents: output performance indicators and evaluation criteria, main factors affecting output performance, output performance improvement methods, etc. Finally, we innovatively propose that TENG can be combined with badminton.